2021
DOI: 10.3390/ijerph18157728
|View full text |Cite
|
Sign up to set email alerts
|

Effects of e-Health Training and Social Support Interventions for Informal Caregivers of People with Dementia—A Narrative Review

Abstract: Along with the burden commonly experienced by informal caregivers (ICs) of people with dementia (PwD), associated with the progressive decline that accompanies dementia, the lockdown due to the public health crisis has had a great negative impact on the emotional wellbeing, physical health, and social relationships of ICs. Support interventions through telemedicine represent an opportunity for ICs to learn the skills required for the care and maintenance of social networks. In this work, a narrative review of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 88 publications
1
20
0
1
Order By: Relevance
“…Given that the adverse health impact of negative social exchanges appears to outweigh the ameliorative impact of positive exchanges, these results have implications for interventions and policy. Specifically, the results suggest that greater focus is needed on reducing the impacts of harmful social interactions, in contrast to a more widely assumed focus of bolstering supportive interactions (Sitges-Maciá et al, 2021).…”
Section: Discussionmentioning
confidence: 79%
“…Given that the adverse health impact of negative social exchanges appears to outweigh the ameliorative impact of positive exchanges, these results have implications for interventions and policy. Specifically, the results suggest that greater focus is needed on reducing the impacts of harmful social interactions, in contrast to a more widely assumed focus of bolstering supportive interactions (Sitges-Maciá et al, 2021).…”
Section: Discussionmentioning
confidence: 79%
“…Evidence shows that telephone-based programs are effective alternatives to in-person support programs (Cothran et al, 2021; Greenberg et al, 2020; Hwang et al, 2021; Kasar & Karaman, 2021; Mok et al, 2020; Sitges-Macia et al, 2021). More so, in the early pandemic, many caregivers were unfamiliar with web-based interfaces such as Zoom or Google Meet, which would have allowed for camera accessibility.…”
Section: Discussionmentioning
confidence: 99%
“…Telephone calls served as an effective and COVID-19 safe method to interact with caregivers who had limited social contact and access to services, including health care (Kasar & Karaman, 2021; Sitges-Macia et al, 2021). In response, a telephone-based intervention was developed to provide emotional support, need-based stress management skills, and COVID-19 safety information.…”
mentioning
confidence: 99%
“…Nevertheless, previous studies exploring whether or not the Tele-Health intervention program could benefit persons with dementia, or MCI and their caregivers, have demonstrated ambiguous results. Some studies found little or no effect of the Tele-health intervention program on caregivers’ burdens, depressive symptoms, and health-related quality of life [ 27 ], and found insignificant improvements in objective caring skills [ 28 ]. Conversely, other research revealed that the Tele-Health intervention program not only improves quality of life and ameliorates neuropsychiatric symptoms in persons with dementia or MCI, but also leads to a better health outcome for primary caregivers of persons with dementia or MCI, a lower risk of mental health impairment [ 29 , 30 , 31 , 32 ], burden reduction [ 29 , 33 ], and improvements in knowledge of dementia [ 29 ].…”
Section: Introductionmentioning
confidence: 99%